Kesesuaian Konsep Akad Fiqh Muamalah dengan Produk Keuangan Syariah Kontemporer: Kajian Normatif atas Fatwa dan Regulasi - Fofi Hanifa Seftiani; Hana Luthfia Widi; Syerly Lia Azharah; Aidil Alfin (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to examine the compatibility of the classical fiqh muamalah contract (akad) concepts with contemporary Islamic financial products in Indonesia. Employing a normative qualitative approach, the research draws upon secondary sources including classical Islamic legal texts, DSN-MUI fatwas, regulations issued by OJK and Bank Indonesia, and related academic literature. The findings reveal that the essential elements of Islamic contracts such as ijab-qabul (offer and acceptance), clarity of the contract object (maḥal al-‘aqd), and the principles of justice and transparency are preserved in the design of modern Islamic financial products. Instruments such as murabahah, musyarakah mutanaqisah, and hybrid contracts like murabahah-wakalah and qardh-ijarah represent adaptive applications that meet market and regulatory needs while remaining within the ethical and legal framework of Islamic law. DSN-MUI fatwas serve as normative references to ensure shariah compliance, while OJK regulations provide the legal-operational framework. Nevertheless, challenges remain, particularly in the uneven capacities of shariah supervision between large banks and smaller financial institutions, as well as in the low level of public literacy regarding Islamic contracts. The study recommends strengthening the synergy between fatwa bodies and regulators, enhancing training and certification for shariah supervisory boards (DPS), and standardizing contract documentation to uphold the integrity of Islamic principles in the evolving financial landscape.